2014
DOI: 10.1108/jedt-09-2011-0057
|View full text |Cite
|
Sign up to set email alerts
|

Design methodology for integrating multipath systems (building services)

Abstract: Purpose: Most multipath delivery systems, such as Building-Services (BSs) are arbitrary distributed with no known solution to reduce the complexity in the way channels are arranged. This paper reports on a geometrical integration methodology that can be used to organise some types of these systems.Methodology: Integration for optimal functionality through reduction of geometrical complexity is achieved by: (i) understanding the elements of complexity within current practices; (ii) identifying commonalities bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Comparing TRIZ methodology with traditional methods inside Engineering design process (EDP), which is a series of steps that engineers follow to generate solutions to a definite design problem, there exist several advantages. Traditional ways of generating product design concepts or solutions could base on the process such as Brainstorming, "Trial and Error" methods, and so on [22,23]. Though such approaches are easy to implement, they tend to lack the innovation essence resulted from core of creativity [24].…”
Section: Advantages Of Triz For Scaffold Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing TRIZ methodology with traditional methods inside Engineering design process (EDP), which is a series of steps that engineers follow to generate solutions to a definite design problem, there exist several advantages. Traditional ways of generating product design concepts or solutions could base on the process such as Brainstorming, "Trial and Error" methods, and so on [22,23]. Though such approaches are easy to implement, they tend to lack the innovation essence resulted from core of creativity [24].…”
Section: Advantages Of Triz For Scaffold Innovationmentioning
confidence: 99%
“…12, 28,31,32,35,36,38,39,40 Separation between the Parts and the whole (system and sub-or super-system) Object has parameter value A at system level, while value B at super-system level (or A at system while B at subsystem level) 1,5,6,7,8,13,14,22,23,25,27,33,35 Table 4.…”
Section: Separation Upon Conditionsmentioning
confidence: 99%
“…Many studies have asserted that design can be an integral resource for an enterprise and a crucial mechanism for integrating product development functions into the serial integral value chain of an enterprise (Fouchal et al , 2014; Luh and Lin, 2012; Vinodh et al , 2012; Vinodh and Rathod, 2014). Additionally, Hsu (2011, 2012) showed that Taiwanese enterprises apply unique product design strategies and methods.…”
Section: Introductionmentioning
confidence: 99%